Formulation and Evaluation of Clindamycin Loaded Biodegradable Dental Cones for Sustained Drug Release in Post-Extraction Management - Kumar, M Pradeep; Prasanna, E Ganga; Yadav, M Mahesh; Babu, B Jagadeesh; Manjula, C.; Patil, Pranav B; Londhe, Samarth Santosh; Mashale, Suraj Ram; Latwade, Rohan Ravsaheb (International Journal of Pharmaceutical Investigation, 2026)
Objectives Dental diseases affect nearly 70% of the global population, often leading to extractions due to periodontitis, caries, or trauma. Post-extraction complications such as bacterial infections, pain, inflammation, and bleeding hinder healing. This study aims to develop clindamycin-loaded dental cones as a localized drug delivery system to manage post-extraction complications effectively. Materials and Methods Dental cones were prepared using gelatin and agar-agar via the mold-filling method. The formulations were evaluated for in vitro drug release, antibacterial efficacy, swelling index, and stability. Drug release kinetics were analyzed using zero-order, first-order, Higuchi, and Korsmeyer-Peppas models. Antibacterial activity was tested against Staphylococcus aureus and Escherichia coli using the agar disc diffusion method. Stability was assessed under refrigeration for one month. Results In vitro drug release studies demonstrated a gradual and controlled release over five days, with the F8 formulation exhibiting the highest cumulative release. Drug release in formulations F7 and F8 ranged from 2.97% to 82.06% and 2.17% to 86.53%, respectively. Antibacterial studies confirmed the effectiveness of these formulations against Staphylococcus aureus and Escherichia coli, highlighting their potential for infection control. Swelling index analysis showed that F8 exhibited the highest swelling (43%), correlating with sustained drug release. Kinetic modeling indicated that drug release followed the Higuchi model and zero-order kinetics, suggesting a controlled diffusion mechanism. Stability evaluations indicated that refrigeration maintained the integrity and effectiveness of the cones over time. Conclusion The biodegradable clindamycin dental cones provide sustained drug release, infection control, and reduced inflammation, offering an alternative to conventional post-extraction treatments while minimizing systemic side effects. Their stability and therapeutic efficacy make them a promising advancement in dental therapeutics.
Keywords: Dental cones; Post-extraction management; Local drug delivery; Clindamycin; Sustained release; Antibacterial efficacy; Dental therapeutics.